PERKAWINAN JANDA TANPA WALI - Paryadi, Paryadi; Nelli, Jumni (Moderation | Journal of Islamic Studies Review, 2021)
One of the pillars of marriage is a guardian. However, according to the Hanafi school, guardians are not in harmony, especially for widows. So there is a case in Balikpapan marriage of a widow without a guardian based on istinbath in the Hanafi School. What is the picture of the marriage and its relevance to marriage without a guardian according to the current context in Indonesia. Researchers use a qualitative approach by using is a case study. In case study research tries to see a case from several sources of data that can reveal the case. Agus and Imah's marriage without a guardian in Balikpapan cannot be justified in Indonesian marriage law, based on the Marriage Law and the KHI. Because the Indonesian government adheres to the Imam Syafii school of thought, which makes guardians a pillar of marriage. Suggestions for the Government to take action on the Marriage Law so that the Marriage Law can be revised again by accommodating the Hanafi School.